JURISPRUDENTIAL ANALYSIS OF COURT DECISIONS IN MARRIAGE ANNOUNCEMENT - Muhammad Ilham (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The court is an institution that plays an important role in resolving civil conflicts, including in the annulment of marriage. Annulment of marriage is one of the legal actions that involves a legal process to decide whether a marriage is valid or not. This study aims to analyze the jurisprudence of court decisions in cases of annulment of marriage. The research method used is the jurisprudence analysis method, which involves collecting and analyzing data from relevant court decisions. In this analysis, we consider the factors that form the basis of the court in deciding to annul a marriage, such as the legal reasons submitted by the parties filing a lawsuit for annulment of marriage. The results of this study indicate that court decisions in cases of annulment of marriage can vary depending on the applicable law in a jurisdiction, the evidence presented, and the legal arguments presented by the parties involved. Some common reasons for annulment of marriage include fraud, domestic violence, the inability of one party to give valid consent, or violations of laws relating to marriage. In addition, this study also identifies legal developments and trends in court decisions related to annulment of marriage, such as changes in legal interpretation or social factors that influence court decisions. In conclusion, this jurisprudential analysis illustrates the complexity and variation in court decisions in cases of annulment of marriage. These decisions are greatly influenced by the facts and laws applicable in each case.